Evaluation of Anticipated Performance Index of Plant Species for Green Belt Development to Mitigate Air Pollution - Sharma, Abhay; Bhardwaj, Satish Kumar; Panda, L. R. Lakshmikanta; Sharma, Abha (International Journal of Bio-resource and Stress Management, 2020)
Anticipated Performance Index (API) is an innovative ecological approach in selecting plant species for reducing air pollution, using Air Pollution Tolerance Index (APTI) and socio-economic parameters. The present study evaluated API of 11 plant species (6 trees and 5 shrubs) for the recommendation of green belt establishment near the national highway expansion region of the Kiratpur-Nerchowk expressway. The scrutiny of the results revealed that the tolerance capacity of plant species along with their performance grade is a justified approach for selecting the most suitable plant species, which can act as sink for air pollution. API on the other hand, can also help to distinguish the sensitive plant species, which can act as bio-monitors. The results showed that among all plant species Leucaena leucocephala and Toona ciliata (API=5) qualify as ‘very good’ performers in green belt development, while Dalbergia sisso (API=4) is a ‘good’ performer. Grewia optiva and Ficus palmata were judged as ‘moderate’ performers (API=3). Whereas, all other remaining investigated trees and shrubs having lesser API values can act as bio-indicators and particularly are very less recommended for green belt establishment. Hence, on the basis of amalgamation of APTI values together with other socio-economic and biological parameters, API significantly is considered as one of the best approaches identified and recommended for long-term refinement of air quality.